Produção de raízes e de ramas e relação entre caracteres da parte aérea e produção de raízes, em variedades de mandioca - de Moura Estevão , Edmundo; Oliveira Begazo, José Carlos Enrique; Starling Brandão , Sylvio; Maffia de Oliveira, Laede (Revista Ceres, 2025)
Ten cassava varieties were studied in Vigosa during the growing seasons of 1966/67 and 1967/68. Root yield and fresh-weight of the aerial parts of the plants were determined. The relationship between some plant aerial characteristics and root yield at harvest were also calculated.